The influence of social exclusion on prosocial behavior of college students: the role of relational need threat and regulatory focus - Hou, Chunna; Li, Shuyu; Shi, Haoling; Liu, Zhijun (Frontiers in Psychology, 2024)
The present study investigated the impact of social exclusion on prosocial behavior, examining the roles of relational need threat and regulatory focus. Utilizing a questionnaire study with 483 participants (Study 1) and an experimental study with 100 participants (Study 2), we found that (1) social exclusion negatively predicted prosocial behavior; (2) relational need threat fully mediated the relationship between social exclusion and prosocial behavior; and (3) regulatory focus, categorized as either promotion or prevention, moderated this relationship in opposite directions. In conclusion, our findings reveal that social exclusion does indeed trigger prosocial behavior. Meanwhile, relational need threat and regulatory focus have a co-action impact on this process. These findings have been carefully discussed within the frameworks of the temporal need-threat model and the cognitive-affective personality system theory.